An Investigation into Brand Perceptions via Customer Reviews - Wu, Xi (2022)
In order to stand out from the mass of brands, it is now essential for companies to acquire and maintain a good brand perception. Many enterprises and scholars have made efforts to obtain brand perceptions, however, the existing methods are either too laborious or do not lead to accurate conclusions. Today's consumer generated content provides an important new information medium for customers throughout the purchase lifecycle, changing the way customers make purchase decisions, and providing a new and better way for companies to understand their customer perceptions. For this reason, this study intends to start with customer reviews, using Amazon Fashion's customer review data to extract customer perceptions of Amazon Fashion. In addition to providing a theoretical contribution to acquiring brand perceptions, this study also provides suggestions on how to improve their customer perceptions and improve the brands’ performance under Amazon Fashion.